1981
DOI: 10.1038/292413a0
|View full text |Cite
|
Sign up to set email alerts
|

Actions of cholera toxin and the prevention and treatment of cholera

Abstract: The drastic intestinal secretion of fluid and electrolytes that is characteristic of cholera is the result of reasonably well understood cellular and biochemical actions of the toxin secreted by Vibrio cholerae. Based on this understanding it is possible to devise new techniques for the treatment and prophylaxis of cholera to complement those based on fluid replacement therapy and sanitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
260
0
3

Year Published

1981
1981
2013
2013

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 512 publications
(265 citation statements)
references
References 93 publications
2
260
0
3
Order By: Relevance
“…treatment with OVA/CTB conjugate is probably largely explained by the effects of the conjugate on gut mucosal APC. Previous studies have shown that conjugation of Ag to CTB, a molecule that binds with high affinity to the GM1 ganglioside receptors present on most cells (30), greatly facilitates Ag uptake and MHC class II-restricted Ag presentation by CD11c ϩ DC as well as other types of APC, such as B cells and macrophages (23). One possibility is that mucosally administered Ag/CTB conjugate preferentially binds to and is taken up by tolerogenic subsets of mucosal DC or other APC.…”
Section: Discussionmentioning
confidence: 99%
“…treatment with OVA/CTB conjugate is probably largely explained by the effects of the conjugate on gut mucosal APC. Previous studies have shown that conjugation of Ag to CTB, a molecule that binds with high affinity to the GM1 ganglioside receptors present on most cells (30), greatly facilitates Ag uptake and MHC class II-restricted Ag presentation by CD11c ϩ DC as well as other types of APC, such as B cells and macrophages (23). One possibility is that mucosally administered Ag/CTB conjugate preferentially binds to and is taken up by tolerogenic subsets of mucosal DC or other APC.…”
Section: Discussionmentioning
confidence: 99%
“…It is now clear that mucosal vaccination can induce both memory IgA + and memory IgG + B cells after oral, intranasal and intravaginal vaccinations [67]. Studies showed protection against infection induced by mucosal vaccines can last for several years, even though intestinal IgA responses vanish after 6-9 months [68][69][70]. For caries vaccines, the duration of salivary IgA responses induced by mucosal immunization need to be explored further.…”
Section: Development Of a Nasal-spray Or Nasal-drop Anti-caries Vaccimentioning
confidence: 99%
“…By comparative studies of the small intestinal mucosa in man, pig and beef we showed that there was a direct relation between the binding ability for cholera toxin and the ganglioside GM1 content [2], which suggested that ganglioside GM1 is the natural specific receptor for cholera toxin. Intestinal mucosa of adult man had a remarkably low concentration of ganglioside GM1 , and it was of importance both from a theoretical point of view, but also for the profylaxis and treatment of cholera and allied intestinal infectious diseases [3] to know the actu,al ganglioside GM1 concentration in intestinal mucosa during development. For the determination of the ganglioside concentration during the fetal stage we used meconium, which is the fist faeces of the newborn and consists mainly of extruded mucosal cells from the intestine.…”
Section: Introductionmentioning
confidence: 99%